(untitled) (Western Pacific Surveillance and Response, 2020)
Influenza preparedness planning by Mongolia Red Cross Society in 2019 has provided a strong foundation for engagement with COVID-19 preparedness and response. The experience underscores the importance and value of investing in epidemic preparedness, and the importance of doing so well in advance of disease outbreaks.